EFFECT OF WASTE FOUNDRY SAND ON INDIRCT TENSIL STRENGTH OF ASPHALT MIXTURE - Ahmed Abdulsattar, Zainab; Abdulhassan Mohammed, Eman (Journal of Engineering and Sustainable Development, 2018)
Laboratory study for the use of recycled foundry sand to improve the performance of asphalt concrete mixture by replacement fine aggregate by waste foundry sand substitute for normal sand was conducted. The experimental work conducted for (4) different proportions (5, 15, 20 and 25)% as fine aggregate . (35) samples was prepared to examine the Marshall stability and flow and moisture damage for asphalt mixture. The obtained results indicate an increase of strength (IDT) for all mixtures than control mixture and higher resist to moisture damage with mixture has(FS (#50).The results showed improvement in behavior in terms of workability and durability and resistance.